Bold approach in finite element simulation on minimum quantity lubrication effect during machining - Ainur Munira, Rosli; Ahmad Shahir, Jamaludin; Mohd Nizar, Mhd Razali; Akira, Hosokawa; Furumoto, Tatsuaki; Mohd Shahril, Osman (Penerbit UMP, 2019)
Application of Minimum Quantity Lubrication (MQL) in cutting process is becoming widespread, whereas manufacturers had gradually turns to the utilization of dry and semi dry cutting during the machining process. Compared to the conventional wet cutting method, utilization of MQL can be considered as parameter sensitive, whereas only a very small amount of cutting fluid is utilized during the process to cater similar or better performance as conventional wet cutting. Thus, it is necessary to understand precisely the characteristic of MQL applied cutting process, where behavior of tool-work/chip interface need to be observed sufficiently, due to its relationship with the cutting performance such as cutting force, cutting temperature, chip morphology, and surface finish. In this paper, bold approach of Finite Element Method (FEM) modelling is proposed in simulating the characteristic of the MQL in machining process. Two interrelated FEM analytical models are designed and executed using the application package software DEFORM™-3D. As a validation, orthogonal cutting tests of medium steel JIS S45C is executed with the TiCN-coated cermet tool in order to evaluate the involved parameter during the application of Minimum Quantity Lubrication in parallel. During the application of MQL in the orthogonal cutting process, three significant variables are observable, which are cutting force, chip thickness and contact length. In this paper, comparison of appearance friction and FEM input friction is done, where it is found that both parameter is related but not similar. Additionally, it is proven that FEM is capable in assessing MQL characteristic with a good degree of accuracy through FEM input friction and chip morphology modelling, thus it is easier to distinguish between contact condition and environmental condition through the proposed FEM validation process.